Semiotika Pesan Dalam Lirik Lagu Berbahasa Daerah “Menas Kamamalo, Mate Kamasuba” - Apolinaris Lake; Fransiska Desiana Setyaningsih; Yoseph Andreas Gual (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
Folk songs are usually written in the local language so that people outside the area sometimes do not understand the lyrics. This condition is one of the reasons for the lack of public interest in listening to folk songs. This is also one of the reasons behind the interest in conducting research related to folk song lyrics. One of the songs that is chosen for the lyrics to be examined is the song of Menas Kamamalo, Mate Kamasuba; it is a very popular folk song especially in Timor Tengah Utara Regency, East Nusa Tenggara. Using Roland Barthes' semiotic approach, this song which consists of six stanzas has a deep and complex meaning. The results of the research show that this song has a message which is a description of various human feelings, which are very complex. At the denotative level, the character “I” in the song has feelings of sadness, anger, disappointment, despair, not appreciated, but on the other hand, at the denotative level, the character “I” in the lyrics of the song has feelings of affection, happiness, love, hope. At the mythical level, the character "I" in the lyrics of the song wants to show that in a relationship there are times when the feelings shown do not always match the reality that is actually felt.